Dogs Owners’ Perception on the Use of Black Soldier Fly, Hermetia illucens L (Diptera: Stratiomyidae) Larvae as an Alternative Source of Protein in Dog Food in Kenya - Ngalo, Susan; Mukhebi, Adrian; Otieno, Kenneth (East African Journal of Agriculture and Biotechnology, 2023)
In recent years, pet owners have begun to show more consideration for their companion animals, which includes paying more attention to their nutrition. This is thought to be a strategy to protect the welfare and health of their animals. As feed and food, using insects has gained increased interest from industry, investigators, policymakers, and the general public globally. Owing to their rapid biomass turnover and dietary value, consideration of insects to serve as novel high-quality protein sources to replace the conventionally used sources for pet foods is gaining momentum. In the formulation of pet foods, ingredients made from black soldier fly larvae (BSFL) are being investigated as sustainable substitutes for traditional animal-derived components. There is, however, limited information about using insects as a source of protein in dog food in Kenya. This study aimed at examining dog owners’ perceptions toward the usage of Black soldier fly larvae protein in dog food. In this study, a structured questionnaire was used to perform a cross-sectional survey among 384 dog owners randomly selected in Kisumu and Nairobi counties, Kenya. In order to determine the key factors associated with the response variables, Frequency distribution analysis, t-tests and chi-square tests were run, while PCA, or principal component analysis, was employed to categorize the various traits of dog owners. Our results showed that dog owners perception of the benefits of BSFL, which had a mean score of 3.795 was significantly higher (t= 136.949; P<0.000) than the overall mean risk score of 3.491 (t= 122.022; P<0.000). This signifies a high degree of acceptance (t= 8.833; P<0.000). The PCA yielded three dimensions with the first component, ‘environmental and economic conditions for rearing BSF’ explaining 31.75% variance; the second component, ‘lack of knowledge of BSF insect’, explaining 25.77% variance while the third component, ‘beneficial properties of BSFL’ explaining 9.83%. The results suggest that BSFLs are generally favourably perceived by dog owners and probable are a substitute to the commonly used sources of protein in dog food.
Keywords: Black Soldier Fly; Larvae; Hermetia Illucens; Dog Owners; Perception; Food Security; Principal Component; Analysis